The application of electrophysiology in the correction of spastic torticollis by triple surgery—report of 96 cases - Jun Wu; Hao Xu; Lu Wang; Jun Li (BMC Musculoskeletal Disorders, 2023)
Abstract Objective To investigate the effect and value of electrophysiology in the ‘triple operation’ (selective excision of spastic muscles in the neck, selective resection of the posterior branch of the cervical nerve and accessory neurotomy) of spastic torticollis. Methods Preoperative electromyography (EMG) examination was performed on 96 patients with spastic torticollis treated in our hospital from January 2015 to December 2019. The results were used to assess the responsible muscles’ primary or secondary position and the function of antagonistic muscles and to formulate a personalised surgical plan. A Cascade PRO 16-channel electrophysiological diagnostic system (produced by Cadwell, USA) was used to record the evoked EMG. Target muscles were denervated under intraoperative electrophysiological monitoring and re-examined by EMG six months later to evaluate the efficacy. Results The satisfactory rate of target muscle denervation was 95%, and the overall good rate was 79.1%. Conclusion Electrophysiological examination and intraoperative application may have a positive value in the selection of the operative method, improving the rate of denervation and evaluating the prognosis of the ‘triple operation’.